The Fundamentals of Child and Adolescent Nursing in Improving Mental and Psychosocial Health among Gender Variant Children in Thailand - Kittiteerasack, Priyoth; Sangngam, Jinnaphat; Matthews, Alicia K (Nursing Science Journal of Thailand, 2018)
Gender variant children including transgender, non-binary and gender non-conforming children represent a significant minority of children requiring proper care from child and adolescent nurses in Thailand. Most of them experience stigmatization and discrimination regarding the lack of social understanding. However, the fundamental knowledge and basic care systems mismatch the corresponding needs of the gender variant children contexts. Also, scant information is available regarding the physical, emotional and psychosocial needs of these children and their care-providers. These limitations induce the high-risk behavior impacting health outcomes or progressing worse health conditions. The purpose of this article is to provide a definition of gender variance in children, to highlight the known physical and mental health care needs of this population, and to provide recommendations for improving the services and care of these children by pediatric nurses in Thailand.